Chenopodium ficifolium flowers under long days without upregulation of FLOWERING LOCUS T (FT) homologs - Štorchová, Helena; Hubáčková, Helena; Abeyawardana, Oushadee A J; Walterová, Jana; Vondráková, Zuzana; Eliášová, Kateřina; Mandák, Bohumil (Planta, 2019)
MAIN CONCLUSION: Chenopodium ficifoliumflowered under long days despite much lower expression ofFLOWERING LOCUS Thomolog than under short days. Frequent duplications of the FLOWERING LOCUS T (FT) gene across various taxonomic lineages resulted in FT paralogs with floral repressor function, whereas others duplicates maintained their floral-promoting role. The FT gene has been confirmed as the inducer of photoperiodic flowering in most angiosperms analyzed to date. We identified all FT homologs in the transcriptome of Chenopodium ficifolium and in the genome of Chenopodium suecicum, which are closely related to diploid progenitors of the tetraploid crop Chenopodium quinoa, and estimated their expression during photoperiodic floral induction. We found that expression of FLOWERING LOCUS T like 1 (FTL1), the ortholog of the sugar beet floral activator BvFT2, correlated with floral induction in C. suecicum and short-day C. ficifolium, but not with floral induction in C. ficifolium with accelerated flowering under long days. This C. ficifolium accession was induced to flowering without the concomitant upregulation of any FT homolog.
Keywords: Magnoliopsida; Gene Expression Regulation, Plant; aktivace transkripce; Transcriptional Activation; Up-Regulation; regulace genové exprese u rostlin; Flowers; Chenopodium; květy; Photoperiod; upregulace; fotoperioda